2007
DOI: 10.1080/19942060.2007.11015194
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Coupled Heat and Mass Transfer in a Trapezoidal Cavity

Abstract: In this paper, we present a numerical three-dimensional study of coupled heat and mass transfer by natural convection occurring in a trapezoidal cavity. Our objective is to evaluate numerically the thermal and hydrodynamic behaviour of this system. It is assumed that the cavity vertical walls are thermally isolated and impermeable, and we imposed on the lower surface a constant high temperature and concentration. The upper surface is supposed to be cooled at a constant temperature and has a zero concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…They used conductive short partition/partitions and they showed that the presence of baffles decreased heat transfer as high as 70%. Other similar studies on natural convection in trapezoidal cavities were done by Peric [13], Van Der Eyden et al [14], Boussaid et al [15], Kumar [16], Papanicolaou and Belessiotis [17], Hammami et al [18], Varol et al [19][20][21] and Natarajan et al [22].…”
Section: Introductionmentioning
confidence: 67%
“…They used conductive short partition/partitions and they showed that the presence of baffles decreased heat transfer as high as 70%. Other similar studies on natural convection in trapezoidal cavities were done by Peric [13], Van Der Eyden et al [14], Boussaid et al [15], Kumar [16], Papanicolaou and Belessiotis [17], Hammami et al [18], Varol et al [19][20][21] and Natarajan et al [22].…”
Section: Introductionmentioning
confidence: 67%
“…Baytas and Pop [7] solved to Darcy and energy equation in cylindrical coordinates using ADI method to analyze natural convection in a trapezoidal enclosure filled with a porous medium. It has been observed that up to Rayleigh number Ra = 100, a conduction-dominated regime prevails, and afterwards a two-cellular convective flow regime takes place at the [14], Peric [15] and Hammami et al [16]. It should be mentioned that in many practical situations, especially those concerned with the design of thermal insulation, conduction in the walls can have an important effect on the natural convection flow in the enclosure.…”
Section: Introductionmentioning
confidence: 96%
“…The rate of propagation of the leading edge effect was given special consideration by them. Moez Hammami et al (2007) studied the coupled heat and mass transfer by natural convection occuring in a trapezoidal cavity. Recently, Rani and Kim (2008) investigated the transient free convection flow over an isothermal vertical cylinder with temperature dependent viscosity.…”
Section: Introductionmentioning
confidence: 99%